2015
DOI: 10.1097/md.0000000000001054
|View full text |Cite
|
Sign up to set email alerts
|

Graz Critical Limb Ischemia Score

Abstract: Critical limb ischemia (CLI), a frequently encountered disorder, is associated with a high rate of limb amputation and mortality. To identify patients at high risk for CLI, we developed a simple risk score for peripheral arterial occlusive disease (PAOD).In our cross-sectional study, we first evaluated 1000 consecutive PAOD patients treated at our institution from 2005 to 2007, documenting clinical symptoms, comorbidities, and concomitant medication. We calculated odds ratios (OR) in a binary logistic regressi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
5
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 24 publications
(26 reference statements)
1
5
0
Order By: Relevance
“…We observed consistent findings after using multiple adjustment methods for confounding covariates. Previous epidemiological data have already suggested a similar association in individuals with and without diabetes [7,8]. The absolute risk of LLE is much higher in longstanding diabetes but, to our knowledge, this is the first longitudinal study supporting an association between diuretic use and LLE in type 2 diabetes.…”
Section: Discussionsupporting
confidence: 64%
See 2 more Smart Citations
“…We observed consistent findings after using multiple adjustment methods for confounding covariates. Previous epidemiological data have already suggested a similar association in individuals with and without diabetes [7,8]. The absolute risk of LLE is much higher in longstanding diabetes but, to our knowledge, this is the first longitudinal study supporting an association between diuretic use and LLE in type 2 diabetes.…”
Section: Discussionsupporting
confidence: 64%
“…However, the design was cross-sectional and other classes of diuretic (loop and potassium-sparing diuretics) were not included in the analyses. In another crosssectional study of 1000 participants with known PAD, a 1.5fold increased risk of critical limb ischaemia with the use of loop diuretics was reported but no information was available regarding other types of diuretic [8]. Randomised controlled trials testing diuretics would have been the best design to assess causality, but relevant reports did not include precise data on LLE, probably because these events are expected to occur infrequently in this setting.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Ueda and colleagues briefly discuss the putative mechanism of the increased risk of amputation with the use of sodium glucose cotransporter 2 inhibitors—namely, volume depletion due to the diuretic effect of this drug class 1. This is in keeping with other studies indicating that standard diuretics are a risk factor for amputation 23…”
mentioning
confidence: 71%
“…35 Previous studies have shown an association between diuretics, both thiazide diuretics and loop diuretics, and lower limb amputation. [36][37][38] If this theory is correct and the association between SGLT2i and amputation is true, then we would expect to be a class effect for all SGLT2i and not limited to canagliflozin.…”
Section: Pathophysiological Mechanismsmentioning
confidence: 97%